Enhancing the weight training experience: a comparison of limb kinematics and EMG activity on three machines - Koyama, Y.; Kobayashi, H.; Suzuki, S.; Enoka, R. M. (European Journal of Applied Physiology, 2010)
The aim of the study was to compare the kinematics and the timing and amount of electromyographic (EMG) activity during the lat-pull down exercise performed on machines that afforded one, two, or three degrees of freedom for the movement. Seven healthy men (age 29.4 ± 5.6 years) participated in the study. The exercise was performed with a 30% 1-RM load. Three types of machines with varying degrees of freedom were used: Type 1, the conventional device that restricted the movement to a frontal plane; Type 2, the addition of forearm supination-pronation; Type 3, the addition of forearm supination-pronation and horizontal extension-flexion about the shoulder. All exercises involved a technique known as beginning movement load (BML) training in which light loads are lifted with a relaxation-lengthening-shortening sequence of muscle activation. The Type-3 machine showed: (1) the greatest vertical displacement of the wrist (p < 0.05); (2) the greatest abduction-adduction displacement about the shoulder (p < 0.01); (3) the least flexion-extension displacement about the elbow joint (p < 0.01); (4) a peak vertical velocity for the shoulder that preceded (p < 0.01) those for the elbow and then wrist during the pull-down phase; (5) a progressive proximal-to-distal sequence of EMG activation involving the serratus anterior, posterior deltoid, latissimus dorsi, and triceps brachii muscles; (6) a reversal of the roles for biceps and triceps brachii during the pull-down phase. These results suggest that BML exercises with greater degrees of freedom can enhance the association between training actions and functional activities.